Produção de trigo duplo propósito e ciclagem de nutrientes em sistema de integração lavoura pecuária - Kozelinski, Salete Mafioletti (2009)
The aim of the present work, carried out at the Agronomist institute of Paraná (IAPAR), experimental unit of Pato Branco-PR, was to evaluate the effect of six grazing periods (0, 21, 42, 63, 84 and 105 days) over the wheat grain production, cultivar BRS Tarumã and its dry matter and animal dung residues decomposition as well as the N, P, K, Ca and Mg release in a crop-livestock system. The experiment was studied in two parts. The first one evaluated the wheat yield components such as number of plants m², number of ear m², number of grain per ear, weight of a thousand grain and hectoliter (pH), weight of six treatments (grazing periods) with two replications laid out as a randomized complete block design. The second phase evaluated the residues decomposition rate and nutrients release using a randomized complete block design with four replication in a factorial scheme being the factor A related to two material (animal dung and wheat dry matter) and factor D referent to different litter bag incubation periods being collected 15, 30, 45, 75, 120 and 204 days after the corn sowing. Were used twenty Purunã steers with average live weight of 162 kg and age of 10 months managed on continuous stocking rate with the aim to keep the forage sward with 25 cm of height. Was noticed a reduction in the number of plants per m², number of ear per m² and grain number per ear as the grazing periods increased what significantly reduced the Dual purpose BRS Tarumã wheat grain production as the grazing period increased. Was also noticed a higher decomposition rate and nutrients release to the wheat biomass when compared to the animal dung, except to Ca, that showed the same tendency to both residues.